Assessing the interactions between learning enjoyment, motivation, burnout, and grit in EFL students: a mixed-methods approach - Yao Song (BMC Psychology)
Abstract This study examines the relationships among Foreign Language Learning Enjoyment (FLLE), L2 grit, academic burnout, and motivated behavior in English as a Foreign Language (EFL) learners, using a mixed-methods approach. A total of 534 Chinese undergraduate EFL learners participated in the quantitative phase, which used a cross-sectional survey, followed by narrative inquiry with 15 participants in the qualitative phase. Structural Equation Modeling (SEM) analysis revealed that FLLE positively influenced motivated behavior while reducing academic burnout. L2 grit mediated the relationships between FLLE, burnout, and motivation, indicating that enjoyment promotes perseverance and resilience. Burnout was found to negatively impact motivation, underscoring the role of emotional well-being in maintaining engagement. The qualitative findings further supported these results, offering insights into learners’ experiences of joy, perseverance, and recovery from burnout. Participants described how moments of enjoyment reignited their long-term motivation, while grit helped them persevere through challenges. Burnout was linked to emotional exhaustion, but positive experiences often helped restore motivation. These findings offer a deeper understanding of the emotional and psychological factors influencing language learning success. The study provides important implications for educators, highlighting the need to create positive learning environments, promote resilience, and address burnout to support students’ sustained commitment to language learning.